Campylobacter jejuni versus Campylobacter coli: Occurrence and antimicrobial resistance in red meat sold in markets in Wasit, Iraq - Kanaan, Manal Hadi Ghaffoori; Tarek, Ahmad M (Journal of Advanced Veterinary and Animal Research, 2025)
Objective: Campylobacters are common causative gastroenteritis pathogens in humans, and they are a leading cause of food poisoning globally. The present investigation sought to assess the occurrence and antibiotic resistance of Campylobacter species recovered from cattle and sheep meat sold in markets in Wasit, Iraq. Materials and Methods: Using conventional microbiological methods, 113 samples were collected from nearby marketplaces and tested to assess the occurrence of Campylobacter. Campylobacter species were confirmed using multiplex polymerase chain reaction. To determine the susceptibility to certain antimicrobial agents, a disk diffusion assay was carried out, and eight different antimicrobial drugs were tested. Results: The findings revealed that Campylobacter’s isolation rate was 10.62%, with 10.77% and 10.42% in cattle and sheep meat samples, respectively. Additionally, 75% of the bacterial isolates were identified as Campylobacter jejuni (C. jejuni), while 25% were confirmed as Campylobacter coli (C. coli). One hundred percent of bacterial isolates exhibited resistance to oxacillin, erythromycin, nalidixic acid, and cloxacillin. Moreover, an abundance of multidrug-resistant Campylobacter species was identified, with eight antibiotypes classified into four categories. Likewise, the bacterial isolates’ multiple antibiotic resistance index ranged from 0.5 to 0.88. Conclusion: According to the current study, cattle and sheep meat pose a potential threat to public health. Therefore, minimizing Campylobacter infection and ensuring the safe use of antibiotics requires strict monitoring, regulatory measures, and suitable treatments. J. Adv. Vet. Anim. Res., 12(3): 774–783, September 2025 http://doi.org/10.5455/javar.2025.l940